2016
DOI: 10.3168/jds.2015-10092
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of phosphorus output in manure and milk by lactating dairy cows

Abstract: Mathematical models for predicting P excretions play a key role in evaluating P use efficiency and monitoring the environmental impact of dairy cows. However, the majority of extant models require feed intake as predictor variable, which is not routinely available at farm level. The objectives of the study were to (1) explore factors explaining heterogeneity in P output; (2) develop a set of empirical models for predicting P output in feces (P f ), manure (P Ma ), and milk (P m , all in g/cow per day) with and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…Feces are the primary route of dietary P excretion (Morse et al, 1992). A meta-analysis by Alvarez-Fuentes et al (2016) showed a clear positive relationship between P intake and fecal P output in dairy cows. Increases in urinary P excretion for DG versus CON were also expected.…”
Section: Phosphorus Utilization and Excretionmentioning
confidence: 99%
“…Feces are the primary route of dietary P excretion (Morse et al, 1992). A meta-analysis by Alvarez-Fuentes et al (2016) showed a clear positive relationship between P intake and fecal P output in dairy cows. Increases in urinary P excretion for DG versus CON were also expected.…”
Section: Phosphorus Utilization and Excretionmentioning
confidence: 99%
“…We conducted a meta-analysis on the impact of increasing corn silage relative to the other silages following the methodology described in Alvarez-Fuentes et al (2016). Forty-seven treatment means of enteric methane emission measurements from lactating cows fed corn silage (17.7%-53.3% of DM) and grass silage (5.5%-53.3% of DM)-based diets in the US and Europe (Dohme et al 2004;Hindrichsen et al 2006;O'Neill et al 2011;van Zijderveld et al 2011avan Zijderveld et al , 2011bHollmann et al 2012Hollmann et al , 2013Brask et al 2013;Haque et al 2014;Reynolds et al 2014;Aguinaga Casañas et al 2015;Livingstone et al 2015;van Gastelen et al 2015) were used.…”
Section: Increasing Corn Silage Content In the Dietmentioning
confidence: 99%
“…Variance of ε ij is assumed to be known and calculated using standard deviation of the treatment means. When standard deviation was not reported, it was estimated with other uncertainty measures reported (e.g., SEM) and N as described in Alvarez-Fuentes et al (2016).…”
mentioning
confidence: 99%